2022
DOI: 10.3390/ijerph19127041
|View full text |Cite
|
Sign up to set email alerts
|

Hesitancy towards the Third Dose of COVID-19 Vaccine among the Younger Generation in Japan

Abstract: The younger generation’s hesitancy towards the COVID-19 vaccine in Japan received significant attention during the early stages of vaccination. However, there is a lack of a comprehensive study in Japan that analyzes the apprehension towards the third dose of vaccine, commonly known as the booster dose, and its underlying causes. Using data from an online panel survey conducted by the Hiroshima Institute of Health Economics Research at Hiroshima University, we examined the severity of booster dose aversion amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Age was a significant predictor of CBVH in 16 studies (38%). Several studies reported that younger people were more likely to be reluctant to accept COVID-19 booster vaccines [ 2 , 4 , 5 , 6 , 8 , 10 , 12 , 25 , 29 , 32 , 36 , 37 , 45 , 52 ]. On the other hand, older individuals were associated with being less hesitant to get boosters [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Age was a significant predictor of CBVH in 16 studies (38%). Several studies reported that younger people were more likely to be reluctant to accept COVID-19 booster vaccines [ 2 , 4 , 5 , 6 , 8 , 10 , 12 , 25 , 29 , 32 , 36 , 37 , 45 , 52 ]. On the other hand, older individuals were associated with being less hesitant to get boosters [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, Bendezu-Quispe et al [ 12 ] found that females are associated with lower booster hesitancy. Moreover, two studies found that males are more hesitant [ 36 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 4 While this discrepancy is in part due to insufficient supply of and access to COVID-19 vaccines, some previously vaccinated people are unwilling or hesitant to get the booster vaccination, even in countries with initially high COVID-19 vaccine uptake. 5 , 6 , 7 , 8 To increase uptake of booster vaccines, most countries inform people about the benefits of boosters, and some countries also employ interventions like sending personal reminders (e.g., Denmark, UK), offering incentives (e.g., Lithuania, many US states), imposing various restrictions on those who have not been boosted (e.g., France, Germany), or even imposing mandates with financial sanctions (e.g., Greece, Malaysia). In addition, non-governmental institutions and companies have adopted similarly heterogenous approaches to increase COVID-19 booster vaccine uptake of their workforce, including financial incentives 9 and mandates.…”
Section: Introductionmentioning
confidence: 99%